1956
DOI: 10.1055/s-0028-1115739
|View full text |Cite
|
Sign up to set email alerts
|

Studien zur Wirkung des Testosterons auf die spermiogenetische Aktivität des Hodens bei Oligospermie

Abstract: Nach l3eobachtungen von H e il e r u. Mitarb. führen hohe Testosterondosen im menschlichen Hoden zunächst zu einer Unterdrückung der Spermiogenese, die jedoch später wieder H e j n k e u. T o n u t t j: Wirkung des Testosterons auf die spermiogenetisdie ÄktlVtt des Hodens Dtsch. med. Wsthx;, 81.3g.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

1957
1957
2009
2009

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…men was observed up to 2 years after treatment. This was confirmed by several authors (Heckel and McDonald -1952;Heinke and Tonutti -1956;Charney -1959;Lamensdorf et al -1975) while others could not recommend rebound therapy in men with sperm counts below 20 millionlml due to the occasional occurrence of patients (2-9%) showing permanently impaired spermatogenesis with sclerosis and hyalinization of the basement membrane and of the tunica propria of the seminiferous tubules (Joel -1960;Tonutti et al -1960;Schirren -1961). However, damage of the tubular architecture could not be confirmed by considering only patients without sclerosis, hyalinization or fibrosis in their testicular biopsies before treatment.…”
Section: Androgensensitive Insufficiency Of Seminal Vesiclesmentioning
confidence: 87%
“…men was observed up to 2 years after treatment. This was confirmed by several authors (Heckel and McDonald -1952;Heinke and Tonutti -1956;Charney -1959;Lamensdorf et al -1975) while others could not recommend rebound therapy in men with sperm counts below 20 millionlml due to the occasional occurrence of patients (2-9%) showing permanently impaired spermatogenesis with sclerosis and hyalinization of the basement membrane and of the tunica propria of the seminiferous tubules (Joel -1960;Tonutti et al -1960;Schirren -1961). However, damage of the tubular architecture could not be confirmed by considering only patients without sclerosis, hyalinization or fibrosis in their testicular biopsies before treatment.…”
Section: Androgensensitive Insufficiency Of Seminal Vesiclesmentioning
confidence: 87%
“…Rebound therapy for fertility disturbances should only be used in special cases of infertility (Joel -1960;Schirren -1975;Heinke et al -1956). Rebound therapy for fertility disturbances should only be used in special cases of infertility (Joel -1960;Schirren -1975;Heinke et al -1956).…”
Section: Discussionmentioning
confidence: 99%
“…It must, however, be mentioned that the patients involved had disturbances of spermatogenesis which manifested themselves as sterility. Rebound therapy for fertility disturbances should only be used in special cases of infertility (Joel -1960;Schirren -1975;Heinke et al -1956).…”
Section: Discussionmentioning
confidence: 99%
“…Other authors treating infertile patients with injectable testoeterone esters have also reported that not all achieve azoospermia (Hecltel & McDonald 1952;Heinke & Tonutti 1956;Spence & Medvei 1959). Rowley & Heller (1972), however, consider the induction of azoospermia necessary for producing the rebound-phenomenon and Charney and Gordon (1978) find that the duration of the azoospermic phase influences the magnitude of the sperm increase thereafter.…”
Section: Discussionmentioning
confidence: 99%